Two new species of Scaptotrigona Moure, 1942 from the Amazon forest (Hymenoptera: Apidae: Meliponini) - Nogueira, David Silva; Santos-Silva, José Augusto dos; Carvalho, Matheus Mourão; Carvalho-Zilse, Gislene Almeida; de Oliveira Alves, Rogério Marcos; Oliveira, Marcio Luiz (EntomoBrasilis, 2022)
The aim of this study was to describe Scaptotrigona nigrohirta sp. nov. and Scaptotrigona hylaeana sp. nov., in order to make their names valid, since at least one of these species has already been widely studied and cited, however, never been formally validated. Also, we have added some comparative notes among some species.